Cytokines and HIV associated neurological manifestations: a systematic review - S. SeyedAlinaghi; A.M. Afsahi; P. Mirzapour; S. Alikarami; A. Afzalian; P. Matini; S. Mahrokhi; Z. Ali; A. Pashaei; S. Eslami; F. Vahedi; P. Paranjkhoo; et al. (Инфекция и иммунитет)
Background. Cytokines are key players in the immune system’s reaction to HIV and play a crucial role in HIV pathogenesis. Dysregulation of cytokines can contribute to the disease’s pathogenesis and associated complications, making a comprehensive understanding of their roles crucial for developing efficacious therapeutic interventions against HIV/AIDS. Therefore, the aim of this systematic review is to examine the role of cytokines in HIV associated neurological manifestations and related complications. Materials and methods. Databases such as PubMed, Scopus, Web of Science, and Embase were explored for original English literature until September 10, 2022. Eligible articles for data extraction were screened and selected in two steps using some inclusion/ exclusion criteria. This study conforms to the PRISMA checklist and Newcastle-Ottawa Scale (NOS). Results. This review included a total of 15 studies. It was identified that cytokines were associated with sleep problems and numerous neurological manifestations. The most common neurological conditions include dementia, seizure, meningitis, cerebral toxoplasmosis, microcephalus, encephalitis, and gliosis. Commonly used cytokines detection methods included PCR, ELISA, Luminex xMAP multiplex platform, and PUREGene DNA Isolation System. Cytokine samples were mostly taken from blood and tissue. Conclusion. There is an interconnecting pathway of cytokines, neurological function (mainly dementia), and sleep habits in people living with HIV. Despite this, the mechanism of cytokines influencing sleep problems and neuropathological disorders remains unclear. Further research is warranted to determine the potential mechanisms and impact of cytokines associations in HIV progression.